Consolidation of Information Resources as a Systemic Base for the Strategic Management of the Enterprises’ Innovativeness - Koleshchuk Orest Ya. (Bìznes Inform, 2019)
The article is aimed at forming the process of consolidation of information resources as a systemic base for the strategic management of the enterprises’ innovativeness. It is defined that in today’s turbulent economic environment, the consolidation of information resources in ensuring the efficient operation of enterprises and improving their level of development is relevant. It is determined that the consolidation of information resources is an important factor leading to the formation of the value-sense paradigm of the enterprises’ activities. The elemental composition of the essence of the concept of «information» is formed. It is disclosed that information resources are transferred in an oral, written or other way; types of information transmission are allocated. It is identified that each enterprise uses a large amount of information resources in its activities; a classification of them is provided. It is defined that the consolidation of information resources is characterized by the fact that at some stage of task solution an aggregate of new information is present that can be compared with a system of own views, concepts, attitudes and assessments. In the future, this updated information will be understood, structured, formalized and will become the systemic base of the strategic management of the enterprises’ innovativeness.